INCORPORATING LITERATURE INTO ENGLISH TEACHING - Mirqodirova , Zilola Shezod qizi (GOLDEN BRAIN, 2024)
Incorporating literature into English teaching lessons is crucial for fostering language proficiency and cultural understanding among students. Exposure to diverse literary works enables learners to engage with complex language structures and vocabulary, enhancing their linguistic competence.